Parameter Transformasi Kurikulum Dayah Salafiyah di Aceh - Tabrani ZA; Saifullah Idris; Ramzi Murziqin; Syahrul Riza; Wahyu Khafidah (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
This study aims to determine the transformation of the Dayah Salafiyah curriculum in Aceh with the research parameter being Dayah Salafiyah MUDI Mesra Samalanga. This research is a descriptive qualitative research, which studies in depth and holistically with the type of field research and uses socio-phenomenological and humanism approaches. This research is process-oriented, which has natural characteristics as a direct data source. Data were collected through interview, observation, and documentation techniques. The validity of the data was checked by using the method and source triangulation technique. While the data analysis technique used is a qualitative inductive analysis technique. The results showed that the curriculum at Dayah MUDI Mesra Samalanga had several components, including: knowledge content objectives, learning experiences, strategies and evaluations. The components of these goals are divided into several levels, namely national educational goals, institutional goals, curricular goals, and instructional goals. The method and education process consists of three levels, namely: Tajhizi, `Aliyah, and Takhassus. Changes in learning materials that have been made have had a very broad impact on the learning process in Dayah in general. Meanwhile, the transformation of learning methods includes two models, namely adaptation and adoption. In addition, in the process of integrating general material and religious material, Dayah is still looking for a new format that is able to accommodate religious knowledge as well as general knowledge, traditionality as well as modernity.